What an original app! : a study on the novelty of software products. Issue 2 (3rd April 2022) - Beghelli, Alejandra; Jones, Sara
ABSTRACT: Innovation in software is important to both members of the public and the software industry, and involves developing software that is both useful and novel. While novelty has attracted significant interest in relation to physical products, it is not so well studied in the context of software products. In this paper, we aim to help develop our understanding of novelty in software by investigating which kinds of software products are seen as more or less novel; what factors may contribute most to perceptions of novelty in software, and whether members of the public and those involved in software development think in the same ways about these things. Through a study consisting of 3 stages, we identify examples of software products that are seen as original, at time of writing, by both software specialists and members of the public, and also two key factors – use of software in a new context, and use of a new underlying technology, which appear to contribute strongly to perceptions of novelty in software. We briefly discuss the implications of our findings and directions for further work.